1973
DOI: 10.1111/j.1528-1157.1973.tb03955.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipropylacetate (Depakine®, Ergenyl®) in the Treatment of Epilepsy

Abstract: SUMMARY A clinical trial with dipropylacetate (DPA), a new anti‐epileptic drug (Dépakine®, Ergenyl®) is reported in 116 patients. Primarily generalized epilepsies ‐ petit mal of different types and centrencephalic grand mal ‐ were mainly benefited. Less favourable results were obtained in epilepsy of focal origin. The side effects were usually minimal, consisting of gastric disturbances. Dipropylacetate increased the effect of other anti‐epileptics, especially barbiturates, primidone and benzodiazepines. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

1975
1975
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 5 publications
2
33
1
Order By: Relevance
“…The alopecia was temporary, not necessitating discontinuation of DPA. Sporadic cases have been observed by others (Kugler et al, 1973;Volzke and Doose, 1973;Klotz, 1974;Penin, 1974), but Kruse (1974) reported that alopecia occurred in 7% of 171 patients treated with DPA.…”
Section: Dermatologicmentioning
confidence: 85%
See 2 more Smart Citations
“…The alopecia was temporary, not necessitating discontinuation of DPA. Sporadic cases have been observed by others (Kugler et al, 1973;Volzke and Doose, 1973;Klotz, 1974;Penin, 1974), but Kruse (1974) reported that alopecia occurred in 7% of 171 patients treated with DPA.…”
Section: Dermatologicmentioning
confidence: 85%
“…Patients receiving DPA in addition to other drugs have been reported rarely to experience slight increases in serum alkaline phosphatase (Suzuki et al, 1972) and transient minor elevations of serum glutamic oxaloacetic transaminase (SGOT) (Volzke and Doose, 1973). There have been no reports of persistent elevations of these enzymes nor of any associated organ damage.…”
Section: Blood Chemistry and Hematologic Abnormalitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, some authors have claimed it exerts a favourable influence on the cognitive state of patients with epilepsy. Following treatment with sodium valproate individuals have been-variously described as being 'more alert', 'more active' and 'more co-operative' and the school performance of children with epilepsy has also been reported to-improve (Volzke & Doose, 1973;Jeavons & Clarke, 1974;Haigh & Forsythe, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…DPA was released for treatment of absence seizures, but it has also been used extensively in infants and in young children with other seizure types [ 15,241, including febrile convulsions [2]. Although the drug was initially considered safe, several reports of toxicity in children attributed to DPA treatment have described cases of acute hepatic failure, Reye syndrome, and pancreatitis 19, 12,22,24). I n spite of its prevalent use in infants and young children, the effects of DPA o n development have not been examined.…”
mentioning
confidence: 99%